2009
DOI: 10.1103/physreva.79.052111
|View full text |Cite
|
Sign up to set email alerts
|

Quantum generalized subsystems

Abstract: We propose a formalism of quantum subsystems for reduced descriptions of quantum systems. This unifies a number of well-known methods and less common approaches. The main mathematical ingredients are completely positive maps and correlation functions. In this formalism generalized quantum systems can be composed and there is a notion of generalized entanglement. Models of fermionic and bosonic systems and also quantum systems described by the SU͑2͒ symmetry are studied.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…There is no unique method of describing the time evolution of open quantum systems and there are several schemes to treat such systems which however typically give rise to non-equivalent dynamics [22,23]. One scheme consists in the derivation of a reduced system dynamics, via tracing over the degrees of freedom of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…There is no unique method of describing the time evolution of open quantum systems and there are several schemes to treat such systems which however typically give rise to non-equivalent dynamics [22,23]. One scheme consists in the derivation of a reduced system dynamics, via tracing over the degrees of freedom of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Only the application of strong magnetic fields (compared to the topological coupling) destabilizes the topological phase [6]. However, several studies [5,7,8,9,10] and a rigorous proof [8] have shown that the toric code (TC) is not stable against thermal excitations, except in four dimensions [5,9].Therefore, the study of active error correction in topological codes [5] is fully justified. Ultimately, the goal is not only to achieve good quantum memories, but also to perform quantum computations with them.…”
mentioning
confidence: 99%
“…The map Γ is completely positive and identity preserving. This description of conditional states fits in the general setting of generalized subsystems of [4].…”
Section: Introductionmentioning
confidence: 71%